PENGARUH KETIDAKAMANAN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA DAN TURNOVER INTENTION KARYAWAN BESAKIH BEACH HOTEL DENPASAR - Widyasari, Ni Made; Dewi, I Gusti Ayu Manuati; Subudi, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
The purpose of this study was to analyze the effects of job insecurity on turnover intention, the effect of compensation on turnover intention, job insecurity influence of job insecurity on job satisfaction, job satisfaction influence on turnover intention, and the influence of compensation on job satisfaction. Samples are taken by 89 employees in Besakih Beach Hotel. Data were collected by distributing questionnaires and using path analysis. The results of this study showed that job insecurity positive effect on turnover intention, compensation negative effect on turnover intention, job insecurity negatively affect job satisfaction, job satisfaction negatively affect turnover intention, and compensation has positive effect on job satisfaction. The implications of this findings are management should taking into account the level of job insecurity by taking into account a comfortable working atmosphere, giving fair compensation, and always improve employee job satisfaction.
Keywords: Job insecurity, compensation, job satisfaction and turnover intention